Dampak Negatif Ketergantungan Berlebihan pada Artificial Intelligence (AI) terhadap Kemampuan Berpikir Kritis dan Pemecahan Masalah Siswa Sekolah Menengah - Husnul Meliyani Zindi Aulia; Erika Zakiah Sholiha; Agung Setyawan (Suria Academic Press, 2025)
Advances in digital technology have introduced Artificial Intelligence (AI) as a significant innovation in education. Its presence offers numerous benefits, from personalized learning toease of accessing information and completing academic assignments. However, despite this positive potential, concerns arise about the negative impacts of excessive AI use by secondary school students, particularly on critical thinking and problem-solving skills. This study aims to examine the negative impact of excessive reliance on AI on secondary school students' critical thinking and problem-solving skills using a literature review approach. Data was obtained from various national and international scientific journals, academic books, and relevant research reports published between 2018 and 2024. The study's results indicate that passive and uncontrolled use of AI weakens students' cognitive engagement in the learning process. Students tend to bypass critical thinking processes such as analysis, synthesis, and evaluation, and miss crucial problem-solving stages such as problem identification, alternative exploration, and independent decision-making. Reliance on instant answers from AI also hinders the development of intuitive thinking and reflective reasoning. Furthermore, a lack of digital literacy among teachers leads to minimal oversight of students' use of AI, further exacerbating the situation. This research recommends the need for education on the wise use of AI, restrictions on its use in certain tasks, and digital literacy training for teachers. With a balanced approach, AI can be used as a learning partner that supports students' cognitive development, not replaces it. Appropriate use of AI will create a balance between technological advancement and strengthening students' intellectual character in the digital age